Carbon Tax Salience and Gasoline Demand - Rivers, Nicholas; Schaufele, Brandon (Université d'Ottawa | University of Ottawa, 2012)
We demonstrate that the carbon tax imposed by the Canadian province of British Columbia, a unique carbon pricing policy that comprehensively applies to all fossil fuels, caused a decline in short-run gasoline demand that is significantly greater than would be expected from an equivalent increase in the market price of gasoline. That the carbon tax is more salient, or yields a larger change in demand than equivalent market price movements, is robust to a range of specifications including intuitively plausible and strong instrumental variables. Along with calculating the reduction in carbon dioxide emissions attributable to the tax, we discuss potential explanations for the differential consumer responses to the carbon tax relative to the market-determined price. / Nous démontrons que la taxe carbone imposée par la province canadienne de Colombie-Britannique, une politique unique qui s'applique complètement à tous les combustibles fossiles, a causé une baisse de la demande d'essence qui est significativement plus élevé que prévu d'une augmentation équivalente de la le prix du marché de l'essence. Que la taxe carbone est plus saillant, ou donne une plus grande variation de la demande que leurs équivalents des mouvements des prix du marché, est robuste à une série de spécifications, y compris intuitivement plausibles et fort variables instrumentales. Ainsi que le calcul de la réduction des émissions de dioxyde de carbone attribuables à la taxe, nous discutons des explications possibles pour les réactions des consommateurs différentielles à la taxe carbone par rapport au prix déterminé par le marché..
Keywords: Carbon tax; tax salience; instrumental variables; environmental pricing; gasoline demand; Taxe carbone; saillance d'impôt; variables instrumentales; taxe environnementale; demande d'essence